Barriers to entry. - Tricks, Henry (Economist, 2025)
The article warns about the potential of artificial intelligence (AI) to destroy the career ladder for junior employees or workers fresh out of college. Findings of a study led by academic and author Eric Brynjolfsson show a decline in employment since 2022 for those aged 22-25 working in AI-exposed roles like customer service and software development. Options that the graduating class of 2026 may consider include increasing their AI literacy and opting for jobs in fields like manufacturing.